Lumbo-pelvic motor control in adolescents with and without low back pain - Astfalck, Roslyn G (Curtin University, 2009)
The prevalence of low back pain (LBP) in the adolescent population is high, with rates approaching adult levels. It has previously been shown that those with LBP during adolescence are at greater risk of experiencing LBP in adult life. Concomitantly, the costs of treating LBP are marked - in Australia direct treatment costs in 2001 were estimated at more than $1 billion/year.Despite the high prevalence and evidence for the progressive development of this condition during adolescence, relatively little is known about the disorder during this life-stage. Previously the disorder in adolescents had been characterised as being dominated by psychosocial factors, despite limited detailed studies in the physical domain. In comparison to the wealth of research investigating LBP in adults, relatively little has been undertaken in adolescence. This is especially true in relation to studies of trunk motor control and the impacts of LBP. Whether results from adult research are transferrable to the younger age group is not known.Prior evidence in adults suggests that non-specific chronic LBP (NSCLBP), where there is no known patho-anatomical diagnosis, should be studied from a biopsychosocial perspective. Previous research in adults has identified several distinct sub-groups of NSCLBP based on differing physical and psychosocial variables. Identification of sub-groups of NSCLBP is recognised as important in research and clinical management. The aim of this doctoral study was to investigate adolescent NSCLBP, the significance and multifactorial nature of this disorder and more specifically to investigate differences in trunk motor control in a detailed laboratory based study of adolescents with and without NSCLBP and sub-groups of NSCLBP. Better information will help inform the development of successful interventions in this age-group and may assist to decrease the societal cost of this disorder across the life-span.This dissertation comprises four studies, comparing adolescents with and without NSCLBP and sub-groups of NSCLBP. First, an investigation of the dimensions of pain, disability and kinesiophobia and associated physical and psychosocial features was undertaken. However the main focus of this doctoral research, the final three studies, was the detailed examination of trunk motor control during sitting, standing and forward bending, all known aggravating factors for NSCLBP. This is the first investigation in an adolescent population of the presence of sub-groups of NSCLBP and the first to investigate physical features in detailed laboratory studies. Further, this is the first study in either an adolescent or adult population to examine spinal regional differences in a lumbar repositioning task.The findings across the four studies showed that adolescents with NSCLBP, before sub-grouping was conducted, had similar levels of pain to previous adult studies, but lower levels of kinesiophobia, disability and duration of pain. Adolescents with NSCLBP had increased experience of stressful family life events, decreased trunk extensor and squat endurance, increased trunk extensor muscle activation in standing and decreased spinal repositioning error compared with healthy adolescents. Results from this dissertation support that, as in adults, NSCLBP in adolescence is a significant health concern and multifactorial in nature. In contrast to prior reports, these adolescent results indicate that for this group with NSCLBP the disorder is dominated by physical factors.The laboratory-based aspects of this research provided evidence that, as in adults, sub-grouping adolescents with NSCLBP based on their pain and motor control patterns demonstrates that they are not a homogenous group. Differences were shown between sub-groups and gender representation, trunk extensor and squat endurance, usual and slump sitting postures, range-of-motion during forward bending, levels of trunk extensor muscle activation in forward bending and spinal repositioning error. In fact, the equal and opposite effect of results between sub-groups for sitting posture and both range-of-motion and trunk extensor activation in forward bending resulted in a wash-out effect when results were pooled for those with NSCLBP. That differences were only noted with sub-grouping supports the importance of doing so in future research.Differences were shown between adolescent and adult data based on regional spinal differences. This was so in sitting posture where NSCLBP in adolescents was shown to be more consistently associated with differences in the upper lumbar spine between sub-groups of NSCLBP and healthy adolescents. Regional differences were also shown in tests of spinal repositioning accuracy, the first study (adolescent or adult) to do so.Differences between adolescent and adult studies were observed for posture, kinematics, trunk muscle activation and variability in spinal repositioning acuity; suggesting that there are inherent differences in the disorder between life-stages. The noted differences between this current study of adolescents and previous adult studies may be due to immaturity of the motor control system, differences in spinal morphology and/or in maturation of the NSCLBP disorder.The dissertation concludes that NSCLBP in adolescence is a significant health disorder and is multifactorial in nature. In this group of adolescents it is dominated by physical factors. Whilst this research was of a small group of adolescents with NSCLBP, results broadly support previous postural and kinematic findings from adult studies. Results for trunk muscle activation and accuracy of spinal repositioning suggest that adolescent NSCLBP is not the same as adult NSCLBP. As in adults the consideration of sub-groups of NSCLBP is central to future research and clinical management of the disorder. This investigation of NSCLBP in adolescence provides a contribution towards understanding the disorder and may help inform the development of targeted interventions. Early intervention in NSCLBP during adolescence may help to decrease the large social cost.